A New Probabilistic Approach Based on Markov Process for Matching Problem. (2016) - Hati, Khalid; Hajjaji, Abdellah El
Abstract: Stereo matching is one of the main topics in computer vision. It consists to find in two images of a same scene, taken from different viewpoints, the pairs of pixels which are the projections of a same scene point. Since the last twenty years, many local and global methods have been proposed to solve this problem. Such stereo configurations reduce the search for correspondences from two-dimensions (the entire image) to one-dimension; the epipolar constraint can be used to facilitate matching by reducing the search. The application area of the matching problem is very wide, including biological sequences, the comparison of different files, speech recognition. In this paper, we will present a new probabilistic approach method based on Markov process for the matching of two epipolar images; where each scan-line is delimited by two successive points of interest.